Foreign Language Teaching Anxiety Among Pre-Service Teachers in Kepulauan Riau - Sayow, Eirene Lady Marchela; Pratiwi, Theodesia Lady; Purba, Hilarius Raditya Priambada (TRANSBAHASA, 2024)
In the realm of language education, the influence of governmental regulations on language programs is substantial, as evidenced by Indonesia’s regulatory framework in Law No. 20/2003. This study examines Foreign Language Teaching Anxiety (FLTA) among pre-service English as a Foreign Language (EFL) teachers during their teaching practicum, focusing on the role of fear of negative evaluation, self-perception of language proficiency, and teaching inexperience. Utilizing a mixed-methods research design, quantitative surveys were conducted with 68 respondents, and qualitative interviews were held with five participants in the Kepulauan Riau area. Results from statistical analyses, including regression, indicate that FLTA has a modest impact on the teaching experience of pre-service teachers. Thematic analyses from qualitative data provide deeper insights into the nuanced interplay of factors contributing to FLTA. The discussion highlights the study’s contributions to the field, advocating for the importance of practical teaching experience, mentorship, and adaptive teaching approaches to mitigate FLTA. This comprehensive approach underscores the necessity of addressing anxiety to enhance the competence and confidence of pre-service English teachers, ultimately contributing to more effective language education.